Contraceptive decision-making in women with migraine: integrating guidelines, vascular risk, and clinical practice - Márk Kozák; Viktor Bencs; Máté Héja; Laszlo Mechtler (Reproductive Health, 2026)
Abstract Purpose of review This narrative review evaluates the relationship between migraine and hormonal contraception, with emphasis on stroke risk, guideline recommendations, and practical clinical decision-making. Special consideration is given to migraine subtypes, estrogen dose, and patient-specific vascular risk factors. Recent findings Migraine with aura (MA) is consistently associated with increased ischemic stroke risk, and combined hormonal contraceptives (CHCs) further amplify this risk. Guidelines uniformly contraindicate CHCs in women with MA, while progestin-only contraceptives (POCs) are considered safe. In migraine without aura (MO), low-dose CHCs (≤ 30 µg EE) may be considered in carefully selected low-risk women, though POCs remain preferable in the presence of vascular comorbidities. Evidence on progestin-only methods, particularly desogestrel, suggests potential improvement in migraine frequency, while data on newer formulations such as drospirenone remain limited. Practical algorithms integrating major and minor vascular risk factors can support individualized contraceptive counseling. Summary Hormonal contraceptive choice in women with migraine requires balancing efficacy with vascular safety. CHCs are contraindicated in MA, while POCs represent the first-line option across most scenarios. For MO, low-dose CHCs may be cautiously considered in the absence of risk factors. Ongoing monitoring and individualized risk stratification are essential to safe decision-making.